OPERATION OF A PHOTOVOLTAIC POWER PLANT BASED ON A HYBRID INVERTER WITH DIFFERENT CAPACITIES OF THE ENERGY STORAGE SYSTEM - KOVAL, VADYM; OROBCHUK, BOGDAN; BUNIAK, OLEH; HETMANIUK, VOLODYMYR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The paper describes the designed and constructed photovoltaic power plant for investigating the operation of an electric energy storage system based on the MUST PV18-5248 PRO hybrid inverter with an installed power of 2320 W of photovoltaic panels. The energy storage system has a voltage of 48 V and is made in two versions with a capacity of 125 Ah and 426 Ah. The effect of capacity on the efficiency of using electricity from photovoltaic panels was investigated. The experimental studies lasted for a year. Graphs of generation and electricity consumption in sunny, moderately cloudy, and cloudy weather were obtained. The results of practical tests indicate that in this case, the battery capacity of 5.55 kWh in the electric energy storage system is not sufficient to accumulate surplus electricity from photovoltaic panels or to supply consumers at night. After analyzing the test results with a storage system with a capacity equal to half of the daily energy consumption, it was found that on sunny days during daylight hours, the electricity generated by the PV plant is sufficient to power the house. However, in the evening, when powered by a solar power plant with a 125 Ah (5.55 kWh) battery, with a consumption of 11 kWh per day, the accumulated electricity is sufficient only up to 21...23 hours. As practical tests show, in the evening in a private house the energy consumption is the highest and this should be taken into account when choosing the capacity of the electric energy storage system. The use of a battery capacity in the electric energy storage system greater than equal to the average daily electricity consumption will provide guaranteed power supply in the evening during sunny days from April to October. To ensure reliable power supply in cloudy weather in summer and winter in the absence of the grid, an additional power source will be required.